Nutritional management of dairy animals for sustained production under heat stress scenario - SINGH, S V; SOMAGOND, YALLAPPA M; DESHPANDE, ADITYA (The Indian Journal of Animal Sciences, 2021)
Dairy industry plays a significant role in the agriculture sector for sustainable growth. Heat stress, on the other hand, has been proven to have a detrimental impact on dairy output in terms of growth, reproductive performance and milk production in dairy animals, especially in tropical areas. Heat stress is one of the most significant issues facing the dairy industry, as rising temperatures and humidity limit animal productivity throughout the summer, resulting in devastating economic repercussions. The purpose of this review is to gather knowledge on the effects of heat stress on dairy output and how to ameliorate them. The diversion of energy resources from the production to the adaptation pathway may be responsible for the loss in productive capacity of dairy animals, when they are exposed to heat stress. There are different approaches pertaining to relieving the adverse effects of heat stress on dairy production system. These approaches may be classified into three major categories viz. genetic, management and nutritional interventions. These approaches might help dairy animals to perform better by reducing the harmful impacts of heat stress. Appropriate shelter design, giving shade, employing sprinklers, installing cooling devices, and using fans and ventilation systems are among the management strategies. The nutritional interventions comprise ration balancing and providing essential micronutrients to improve the productive and reproductive performance. Some of the most widely used dietary measures to ensure optimal production are inclusion of protein or fat (prill fat), micronutrients antioxidants (vitamins and minerals) and some feed additives (Astaxanthin, betaine, melatonin, Chlorophytum borivilianum) in the diet. These antioxidants and feed additives can be used to attenuate the negative effects of environmental stress. Furthermore, providing adequate energy and antioxidants help to ensure optimum growth, milk production and reproduction efficiency during heat stress. This review provides an overview of the consequences of heat stress on dairy animals, emphasizes essential nutritional strategies for heat stress reduction in dairy animals, and evaluates the influence of various feed supplements on growth, productivity and physiology.